How could agricultural trade between Ukraine and the EU benefit from institutional harmonization? - Rusetska, Uliana (2014)
Trade liberalization as a part of European integration has been on the Ukrainian agenda for years and resulted in the finalized Deep and Comprehensive Free Trade Area (DCFTA) agreement with the EU, though yet to be signed. This thesis aims to contribute to the previous assessments by approaching the issue of institutional alignment of Ukraine to the EU’s acquis stemming from the “deep” aspect of the DCFTA. The “small shares” problem inherent in previous applications of the Computable General Equilibrium model to study Ukraine-EU trade liberalization is addressed here by estimating potential Ukrainian exports of currently negligibly traded meat and dairy products with the EU. This is done by applying the Sharp Regression Discontinuity design to estimate the treatment effects from a representative adjustment experienced by the New Member States of the EU. The findings reveal a significant positive discontinuity of exports for new EU members for all meat and dairy product categories with particularly large increase of bovine products’ exports. Final calculations demonstrate the most pronounced potential growth of Ukrainian exports to the EU to accrue for animal products as well as milk and dairy produce, up to 149 and 33 million Euros respectively.